Nurses and health‐promoting self‐care: Do we practice what we preach?. (31st October 2018) - Ross, Alyson; Yang, Li; Wehrlen, Leslie; Perez, Avery; Farmer, Nicole; Bevans, Margaret
Abstract: Aims: To examine the health‐promoting behaviours performed by registered nurses (RNs), as well as workplace factors that influence participation in those behaviours. Background: Nurses have high levels of overweight/obesity and may not be engaging in health‐promoting self‐care. Methods: A cross‐sectional Web‐based survey collected information from 335 RNs regarding their physical activity, sedentariness and fruit/vegetable consumption. Results: More than half were overweight (34.1%) or obese (23.4%), and 80.1% were "sedentary" (≥3 hr sitting/day), particularly those working outside of direct patient care in management, research and education. Only 47.2% consumed 5+ servings of fruits/vegetables daily. Nurses who enjoyed their jobs (higher levels of compassion satisfaction) reported higher levels of physical activity ( p = 0.03) and fruit/vegetable consumption ( p = 0.02). Conclusion: RNs who work outside of direct patient care might be at increased risk for sedentariness and obesity. RNs who enjoy their jobs may experience less stress and have more energy to exercise and to prepare/consume healthy meals. Implications for Nursing Management: Nurse managers should practice self‐care by engaging in exercise, proper nutrition and demonstrating work–life balance, both to protect their own health and to serve as role models for RNs in direct patient care.